Characteristics of Organizational-Pedagogical Conditions which are the Basis of Forming Readiness of the Future Nursing Bachelors to Professional Activity - Natalia Lisna-Miskiv (Pedagogical Discourse, 2017)
The article substantiates the expediency of introduction in the educational process the professional training of future nursing bachelors organizational and pedagogical conditions. It was found that the need to introduce in the educational process of higher medical institutions some additional psychological and educational factors was dictated by the lack of adequate tools and effective methodical techniques that can improve the quality of professional training of future nursing bachelors. The attention is focused on the fact that organizational and pedagogical conditions are additional psychological and pedagogical factors that are introduced in the educational environment of higher medical institution to integrate practical measures. It is proved that the organizational and pedagogical conditions provide significant improvement of the state of readiness of future nursing bachelors to professional activity. During the research a working hypothesis that the praxeological approach should be on the basis for selection of organizational and pedagogical conditions was put forward. Choosing praxeological approach, we have considerated that the effectiveness of educational activity of future bachelors must meet rationality, efficiency, economy and intensity. We believe that the praxeological approach has great potential to organize educational activity. Therefore, the use of praxeological approach to professional training of future nursing bachelors allows to study in practice the methods of implementation of effective professional activity and make practical recommendations for its improvement.In the context of the praxeological approach four organizational and pedagogical conditions were chosen. These include: 1) the individualization of student learning as a factor in the formation of motivational valuable sphere of future nursing bachelors; 2) the systematic organization of integrative medical knowledge in the educational environment of higher medical institutions; 3) the formation of productive clinical experience of students of medical institutions in terms of teaching and undergraduate practices; 4) the use of gaming simulation methods in formation of personal competence of nursing bachelors.In practical context when selecting organizational and pedagogical conditions, two factors were taken into account. Firstly, all chosen organizational and pedagogical conditions were conformable to the principles of praxeology and met fully the requirements of praxeological approach. Secondly, each of the four organizational and pedagogical conditions had a significant impact on the formation of indicators of specific component (motivational valuable, theoretical cognitive, practical connatative, personality-reflective) of readiness of future nursing bachelors to professional activity.Key words: organizational and pedagogical conditions, praxeological approach, professional training, future nurses.